Nuclear morphometry in columnar cell lesions of the breast: is it useful?. Issue 12 (7th April 2006) - Lim, C N; Ho, B C S; Bay, B H; Yip, G; Tan, P H
Abstract : Aims: To evaluate the nuclear morphometric features of breast columnar cell lesions (CCLs) observed on mammotome core biopsies, to determine if there are significant measurable differences between those with atypia and those without. Correlation with follow-up open excision specimens was made. Methods: Mammotome core biopsies performed on patients that contained CCLs were derived from the departmental case files. Histological material was reviewed and foci of CCLs demarcated for nuclear morphometric assessment, which was accomplished using an imaging system. Nuclear parameters studied were nuclear area and perimeter, circularity factor and feret's diameter. Statistical analysis used the GraphPad Prism software, with p<0.05 indicating significance. Results: On examination of core biopsies of 40 patients with CCLs, 8 lesions were benign, 4 showed atypical lobular hyperplasia, 8 showed CCLs with nuclear atypia, 19 disclosed atypical ductal hyperplasia (ADH) and 1 showed ductal carcinoma in situ (DCIS). The nuclear area, perimeter and feret's diameter of CCLs with atypia were significantly greater than those without (p = 0.04, 0.03 and 0.019, respectively), whereas no difference was observed in the circularity factor. Follow-up open excision biopsy specimens in 24 patients showed upgrading to DCIS in 40% of cases diagnosed initially with ADH on core biopsy compared with 20% of CCLs with atypia. Conclusions: Nuclear morphometry in CCLs confirms nuclear size as the key parameter in the assessment of nuclear atypia. Whether it can be potentially used as an adjunctive tool depends on the establishment of appropriate cut-offs.